What can we learn from competition analysis? - Mason, B.; Cossor, J. (coachesinfo.com, 2000)
An analysis of the 1999 Pan Pacific Swimming Championship competition analysis data from Sydney indicated that the relationship between the quality of the swim performance and stroke length was not significant as is commonly assumed in swimming arenas, apart from a few events. The average free swimming speed was significantly correlated to race results for all events, but this was to be expected. The next most highly correlated variable with race performance was the turn time, which was significant in 92% of all events. Start and turn times along with free swimming speed were considered significant in all of the form strokes. This was similar to the freestyle events but these races also showed that the finish time was an important part of obtaining a good race result. The second half of the race was more strongly related to race performance than the first half of the distance races in all events except for the women's 400m Freestyle. In the individual medley events, turn performance was significantly related to race performance. It was found that the most significant individual stroke within the medley races was breaststroke followed by backstroke, butterfly and freestyle. The above information is considered accurate for elite level swimmers and can be used to develop a general competition model. It should be remembered that the information is based on the top eight or 16 swimmers in each event so may not be specific to a particular swimmer and that the final competition model should be suited to the individual.